Individualized Template MRI Is a Valid and Reliable Alternative to Individual MRI for Spatial Tracking in Navigated TMS Studies in Healthy Subjects - Fleischmann, Robert; Köhn, Arvid; Tränkner, Steffi; Brandt, Stephan A.; Schmidt, Sein (Frontiers in Human Neuroscience, 2020)
# Objectives: Navigated transcranial magnetic stimulation (nTMS) provides significant benefits over classic TMS. Yet, acquisition of individual structural magnetic resonance images (MRIindividual) is a time consuming, expensive and not in all subjects feasible prerequisite for spatial tracking and anatomical guidance in nTMS studies. We hypothesize that spatial transformation can be used to adjust MRI templates to individual head shapes (MRIwarped), and that TMS parameters do not differ between nTMS using MRIindividual or MRIwarped. # Materials and Methods: Twenty identical TMS sessions, each including four different navigation conditions, were conducted in ten healthy subjects (1 female, 27.4±3.8 years), i.e. twice per subject by two researchers to additionally assess interrater reliabilities. MRIindividual were acquired for all subjects. MRIwarped were obtained through spatial transformation of a template MRI following a 5-, 9-and 36-point head surface registration (MRIwarped_5, MRIwarped_9, MRIwarped_36). Stimulation hotspot locations, resting motor threshold (RMT), 500µV motor threshold (500µV-MT) and mean absolute motor evoked potential difference (MAD) of primary motor cortex (M1) examinations were compared between nTMS using either MRIwarped variants or MRIindividual and non-navigated TMS. # Results: M1 hotspots were spatially consistent between MRIindividual and MRIwarped_36 (insignificant deviation by 4.79±2.62 mm). MEP thresholds and variance were also equivalent between MRIindividual and MRIwarped_36 with mean differences of RMT by -.05±2.28% maximum stimulator output (%MSO) (t(19)=-.09, p=.923), 500µV-MT by -.15±1.63 %MSO (t(19)=-.41, p=.686) and MAD by 70.5±214.38 µV (t(19)=1.47, p=.158). Intraclass correlations of motor thresholds were between .88 and .97. #Conclusions: NTMS examinations of M1 yield equivalent topographical and functional results using MRIindividual and MRIwarped if a sufficient number of registration points is used.